Relationships between maternal emotional expressiveness and children's sensitivity to teacher criticism - Mizokawa, Ai (Frontiers in Psychology, 2013)
Caregivers’ emotional responses to children influence children’s social and emotional development. This study investigated the association between maternal emotional expressiveness in the context of mother–child interactions and young children’s sensitivity to teacher criticism. Sensitivity to teacher criticism was assessed among 53 Japanese preschoolers using hypothetical scenarios in which a puppet child representing the participant made a small error, and a puppet teacher pointed out the error. Self-report questionnaires were used to measure maternal expressiveness. The results demonstrated that negative maternal expressiveness toward one’s own children was positively related to children’s ratings of their own ability and negatively related to children’s motivation to continue with the task after teacher criticism. Positive maternal expressiveness was not related to children’s sensitivity to criticism. These findings suggest that children who have experienced more negative emotion from mothers may be more likely to hold negative beliefs about how others will respond to their behavior more generally. This may, in turn, lead to a defensively positive view of one’s own abilities and a disinclination to persevere as protection from additional opportunities for teacher evaluation.